PENERAPAN METODE TALAQI DALAM PEMBELAJARAN ALQURAN DI RUMAH TAHFIDZ FATHUL QURAN AZ-ZAHRA TULUNGAGUNG - Wahyuningsih Kader; Siti Nur Hidayatul Hasanah (LPPM STAI Muhammadiyah Probolinggo, 2024)
Based on data from the Indonesian Mosque Council (MUI), 72 percent of Indonesian Muslims are illiterate in the Koran. This data can be proven that learning the Koran, especially in Indonesia, is very minimal. This can be caused by several factors, including a lack of motivation to read the Koran, or the method used is not appropriate to the condition of the individual being taught so that learning the Koran is difficult. This research aims to find out the process of implementing the Talaqi Method, the inhibiting and supporting factors in implementing the Talaqin Method and what the solutions are for overcoming obstacles to implementing the Talaqi Method. This type of research uses qualitative research methods with a descriptive approach. The data collection techniques that researchers use are interviews, observation, documentation. Source of data for boarding school caregivers and students. The results of the research show that the application of the talaqi method in learning the Koran at Tahfidz Fathul Quran Az-Zahra's home is: a) dividing the study group into two classes, namely the Iqro class and the Koran class b) there are differences or changes from the previous Quraan reading. c) Mothers are more focused because the Ustadzah gives an example of reading directly d) Mothers can already see where their mistakes are e) are easy to accept and can understand how to read the Koran according to the Tajwid. f) can read 1 Juz per day.